A Foster Mother Can be a “Biological Mother” in Raising Neglected Children by Applying Family Based-Care in Yayasan SOS Children’s Village, Indonesia - Rizabuana Ismail; Harisa Putri (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
The purpose of this study was to analyze the application of the family-based care model at the Yayasan SOS Children's Village, Indonesia. SOS Children's Village is a non-governmental organization engaged in family-based care for those who have lost the love and care of their nuclear family. This study uses a descriptive qualitative and quantitative approach by interviewing six foster mothers and other 36 respondents who live in the SOS Children's Village. The results of this study indicate that the family-based care model is considered very appropriate to be applied to neglected children. Foster mothers are women who replace the role of biological parents in providing family function. The SOS family is formed without any blood ties. The relationship between foster mothers and children is very intimate as if they were biological families. Sociologically, the function of the family is carried out well in this foundation, although this function is only received by children from a foster mother and the foundation. This paper concludes that the family-based care implemented by the SOS Children Village Foundation is very good in educating neglected children so that they can shape the character of children who are religious, polite, and independent.